Design of 1-bit and 2-bit magnitude comparators using electro-optic effect in Mach–Zehnder interferometers - Kumar, Santosh; Bisht, Ashish; Singh, Gurdeep; Choudhary, Kuldeep; Raina, K.K.; Amphawan, Angela (Elsevier B.V., 2015)
The Mach–Zehnder interferometer (MZI) structures collectively show powerful capability in switching an input optical signal to a desired output port from a collection of output ports. Hence, it is possible to construct complex optical combinational digital circuits using the electro-optic effect constituting MZI structure as a basic building block. Optical switches have been designed for 1-bit and 2-bit magnitude comparators based on electro-optic effect using Mach–Zehnder interferometers. The paper constitutes a mathematical description of the proposed device and thereafter simulation using MATLAB. Analysis of some factors influencing the performances of proposed device has been discussed properly. The study is verified using beam propagation method.